Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1177/1548051812465895
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese–Canadian Cross-Cultural Investigation of Transformational Leadership, Autonomous Motivation, and Collectivistic Value

Abstract: Synthesizing theories of transformational leadership and self-determination, this research investigated whether transformational leaders (a) promote the autonomous motivation of their subordinates and whether (b) it results in higher autonomous motivation when subordinates hold high collectivistic values. Multilevel data were obtained from work samples in China and Canada. The results showed a positive relation between managers' transformational leadership and subordinates' autonomous motivation cross-cultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 57 publications
(74 reference statements)
3
29
0
Order By: Relevance
“…In general, the study found that the four components that make up the motivation factor structure do not neatly follow the findings from Western festival motivational studies given the strong pull of the event in general, the importance of family togetherness, and the cultural exploration through interaction/socialization. Although the study did not seek to assess prevailing cultural values, the participating sample supported aspirational and collectivist values, though some of these values are changing in the younger generations (e.g., Wang & Gagné, 2013). The study results point to the strength of family, and indicate female attendees place a greater significance on the family and known group togetherness component than other attendees.…”
Section: Discussionmentioning
confidence: 79%
“…In general, the study found that the four components that make up the motivation factor structure do not neatly follow the findings from Western festival motivational studies given the strong pull of the event in general, the importance of family togetherness, and the cultural exploration through interaction/socialization. Although the study did not seek to assess prevailing cultural values, the participating sample supported aspirational and collectivist values, though some of these values are changing in the younger generations (e.g., Wang & Gagné, 2013). The study results point to the strength of family, and indicate female attendees place a greater significance on the family and known group togetherness component than other attendees.…”
Section: Discussionmentioning
confidence: 79%
“…with autonomy support; Wang & Gagné, 2013) would be positively related to both forms of autonomous motivation, unrelated to any form of controlled motivation, and negatively related to amotivation. Contingent reward leadership should be positively related to both controlled and autonomous forms of motivation, and negatively related to amotivation, because items measuring contingent reward leadership focus exclusively on providing clear directions and positive feedback in exchange for performance (Bass & Riggio, 2006).…”
Section: Testing For Convergent and Discriminant Validitymentioning
confidence: 97%
“…Specifically, the nine countries (i.e., Canada, Belgium, France, Senegal, United Kingdom, Norway, Switzerland, China, and Indonesia) in which data were collected varied in terms of cultural background, economic situation, political regime, and labour conditions, but the samples also varied in terms of industry, organizational structure, and jobs. Though we did not assess prevailing cultural values, Hofstede's (2001) studies point out that the participating samples vary in terms of collectivism and power distance, though some of these values are changing in the younger generations (e.g., Wang & Gagné, 2013). We begin with providing a description of SDT and describing the new scale before testing its validity.…”
mentioning
confidence: 99%
“…Bass and Riggio (2006) indicate that transformational leadership style aligns with collectivist values, but only conflicts when there is hierarchy and centralized decision making, in which case a transactional leadership style is likely to prevail. In a cross-cultural study of Canadians and Chinese, Wang and Gagné (2013) found a positive relationship between transformational leadership and followers' autonomous motivation when the subordinates held collectivist values. Jung and Avolio (1999) found that collectivists performed better with transformational leaders and individualists performed better with transactional leaders, an indication that a diversity of styles can have positive results.…”
Section: Do Chinese Canadians Lead Differently Than Non-asian Leaders?mentioning
confidence: 99%